Cover Image, Volume 66, Issue 3. Issue 3 (March 2017) - Sparnacci, Katia; Antonioli, Diego; Perego, Michele; Giammaria, Tommaso Jacopo; Seguini, Gabriele; Ferrarese Lupi, Federico; Zuccheri, Giampaolo; Gianotti, Valentina; Laus, Michele
Abstract : The cover image, by Katia Sparnacci et al., is based on the Research Article High temperature surface neutralization process with random copolymers for block copolymer self‐assembly, DOI:10.1002/pi.5285 . Abstract : The cover image, by Katia Sparnacci et al., is based on the Research Article High temperature surface neutralization process with random copolymers for block copolymer self‐assembly, DOI:10.1002/pi.5285 .